Occurrence of emerging multiresistant pathogens in the production chain of artisanal goat coalho cheese in Brazil. (May 2022) - Aragão, Breno Bezerra; Trajano, Sabrina Cândido; de Oliveira, Raylson Pereira; da Conceição Carvalho, Maria; de Carvalho, Rafaella Grenfell; Juliano, Maria Aparecida; Junior, José Wilton Pinheiro; Mota, Rinaldo Aparecido
Abstract: Sanitary-hygienic failures in cheese making can pose health risks to consumers. This study aimed to identify multiresistant pathogens in different production stages of artisanal goat coalho cheese in Brazil and characterize their phenotypic and genotypic resistance. Eleven properties in the state of Pernambuco, Brazil, participated in the study. Samples were obtained from different stages of production and the humans involved. The samples obtained were submitted to microbiological culture, then all the isolated microorganisms were submitted to the Matrix Associated Laser Desorption-Ionization - Time of Flight technique for the microbiological identification of the species. Subsequently, Staphylococcus spp., Enterococcus spp. and Macrococcus caseolyticus were subjected to polymerase chain reaction to search for resistance genes and disc diffusion technique to evaluate the resistance profile. A total of 111 isolates were obtained and 31 species were identified, with the frequency of Staphylococcus spp. (62.20%; 69/111), Enterococcus spp. (11.60%; 13/111), Macrococcus caseolyticus (10%; 11/111), Bacillus spp. (3.60%; 4/111), Enterobacter spp. (3.60%; 4/111), Aureobasidium pullulans (1.80%; 2/111), Corynebacterium camporealensis (1.80%; 2/111), Issatchenkia occidentalis (1.80%; 2/111), Kocuria kristinae (1.80%; 2/111), Aerococcus viridans (0.90%; 1/111) and Filifactor villosus (0.90%; 1/111). Phenotypic and genotypic resistance was also detected with the occurrence of 15.90% (7/44) of the mecA gene, 4% (1/25) vanA, and 4% (1/25) vanB in Staphylococcus spp. and 20% (2/10) vanB in and Enterococcus spp. Emerging multiresistant pathogens are present in the production chain of artisanal goat cheese and humans, who exert an important role in disseminating these bacteria with imminent risks to human health. Highlights: Multiresistant emerging pathogens, a danger to human and animal health. Multiresistant zoonotic pathogens emerging in the goat cheese production environment. Staphylococcus spp. identified in the cheese production environment and in humans. Detection of Staphylococcus spp. resistant to methicillin and vancomycin.